A comparison of the academic performance of nonnative English-speaking (ESL) and native English-speaking graduating seniors in EET programs on DeVry University Chicago area campuses - Lan, Shi "Stan", author; Gloeckner, Gene W., advisor; Morgan, George A., advisor; Lehmann, Jean P., committee member; Esfahani, Rasoul, committee member (Colorado State University. Libraries, 2004)
This dissertation compared academic performance of nonnative English-speaking graduating seniors and native English-speaking graduating seniors in the Electronics Engineering Technology (EET) programs at DeVry University. In addition, graduating seniors with different ethnic origins (Asian, Hispanic, and other) were compared in regard to their performance measured by the DeVry EET assessment instrument and their cumulative GPAs in various course sequences. The study used 2X3 factorial analyses of variance, paired t tests, and multiple regression. The actual sample was collected from the graduating classes of the EET programs on DeVry University Chicago area campuses. The sample was further divided into three nonnative English-speaking ethnic groups (Asian, Hispanic, and others) and three native English-speaking ethnic groups (Asian, Hispanic, and others). All nonnative English-speaking students came from countries where English is not the primary language spoken; they were mainly resident aliens or on student visas; many of them were remedial ESL course takers. In general, both native English-speaking and normative English-speaking graduating seniors performed equally well in DeVry's practical, "hands-on" EET programs. The study showed that, within DeVry's technology programs, students of Hispanic origin performed equally well, instead of doing poorly compared to students of other ethnic origins, as has been reported in the reviews of the literature. The study found that native English-speakers performed better than nonnative English-speakers in oral/written communications, measured by the assessment instrument and students' GPAs in the English/humanities courses. Paired t tests showed that normative English-speaking graduating seniors' GPAs in the English/humanities course sequence were significantly lower than their GPAs in the technical course sequence. This study also found, for graduating seniors sampled, that normative English-speakers had higher cumulative GPAs in the engineering technology course sequence than native English-speakers. The possible contributing factors to this finding were discussed. This research provides a better understanding of how students from different language and ethnic backgrounds are doing in college and how to facilitate their learning within practical technology programs at a career oriented for-profit university.
Keywords: multicultural education; higher education